Czy wiedza i kultura humanistyczna potrzebna jest współczesnemu człowiekowi? - Piotrowska, Ewa (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
Technological progress and achievements are fundamental to social and economic progress. On the other hand however, they pose a threat to men, who fail to keep abreast of the pace and the results of the changes that take place. Science and education play therefore a crucial role in preventing the most significant problems. Dehumanisation is a real threat to the contemporary man. By means of analysing historical conditions for creating the term ‚Bildung’, in particular in Germany, I draw attention to how this idea could possibly be an alternative to the modern man.